Pengaruh Suku Bunga, Kurs Rill dan Pertumbuhan Ekonomi Terhadap Yield Obligasi Pemerintah: Lower Middel Income Countries di Asia Pasifik - Lara Yuli Rusdy; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study explains the influence of monetary policy interest rates, real exchange rates and economic growth on government bond yields on Lower Middle Income Countries in Asia Pacific. This study combines cross section data in 5 countries with time series from 2007-2018, with the Panel Regression method and the Random Effect model selection test. The results show that: (1) Monetary Policy Interest Rates have a negative and significant effect on government bond yields on Lower Middle Income Countries in Asia Pacific, (2) The real exchange rate has a positive and insignificant effect on government bond yields for Lower Middle Income Countries in Asia Pacific. , (3) Economic growth has a negative and significant effect on government bond yields on Lower Middle Income Countries in Asia Pacific.